ANALISIS PENGARUH MARKETING MIXTERHADAP CUSTOMER VALUE DI PELAYANAN RAWAT JALAN PUSKESMAS KEDUNGDORO - Slamet Imam Syafi’I; Achmad Daeng GS; Bambang Karnain (Fakultas Ekonomi Universitas 45 Surabaya, 2022)
The number of patient visits at the Kedungdoro Health Center from 2019 to 2021 has decreased, both old and new patient visits. These conditions indicate that patient loyalty is low, the low patient loyalty can occur due to patient dissatisfaction which is influenced by the marketing mix. The purpose of this study was to determine the effect of the marketing mix, namely products, people, processes and physical evidence on customer value at the Kedungdoro Health Center.This study is a quantitative study with a cross-sectional study design. The study population was all patients in November as many as 1849 patients. The research sample was 178 patients and was taken by purposive sampling method. Data were collected by using a questionnaire instrument and analyzed by Multiple Linear Regression.The results of the research on hypothesis testing showed that the results of the t-test of the product, people, process and physical evidence variables partially had a significant positive effect on the customer value variable. In addition, the F test results show that all elements of the marketing mix (products, people, processes and physical evidence) simultaneously or simultaneously have a significant effect on customer value. Elements of the marketing mix that need to be evaluated in order to increase patient loyalty are people and physical evidence